2016
DOI: 10.1016/j.colsurfa.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Transverse magnetic field driven modification in unsteady peristaltic transport with electrical double layer effects

Abstract: The influence of transverse magnetic field on time-dependent peristaltic transport of electrically-conducting fluids through a microchannel under an applied external electric field with induced electric field effect is considered, based on lubrication theory approximations.The electrohydrodynamic (EHD) problem is also simplified under the Debye linearization.Closed-form solutions for the linearized dimensionless boundary value problem are derived.With increasing Hartmann number, the formation of bolus in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 45 publications
1
28
0
1
Order By: Relevance
“…Consider two-dimensional peristaltic flow (̃,̃) of an unsteady incompressible Carreau fluid through a wavy micro-channel, shown in Figure 1. Mathematically, wall deformation in the microchannel is expressed as [23]:…”
Section: Flow Regimementioning
confidence: 99%
“…Consider two-dimensional peristaltic flow (̃,̃) of an unsteady incompressible Carreau fluid through a wavy micro-channel, shown in Figure 1. Mathematically, wall deformation in the microchannel is expressed as [23]:…”
Section: Flow Regimementioning
confidence: 99%
“…This model however constitutes a relatively simple formulation for analyzing electro-peristaltic transport. In this direction, some more recent investigations [20][21][22][23][24][25] have been reported to analyze the electro-peristaltic transport with channel flow [20], capillary flow [21], power law fluids [22], couple stress fluid [23], magnetohydrodynamics [24], Viscoelastic fluids [25]. They have concluded that peristaltic transport/physiological flow may be controlled by adding and opposing the external electric field.…”
Section: Introductionmentioning
confidence: 99%
“…It involves the motion of ionized particles/molecules as well as their interactions with electric fields and surrounding fluid. EHD applications encompass biological transport, desalination, ion drag pumps in spacecraft propulsion, fuel‐emulsion mixing optimization, and bio‐materials processing . The application of EHD to heat transfer and mass transport problems also has applications with certain energy system restrictions that require enhanced heat transfer and mass transport.…”
Section: Introductionmentioning
confidence: 99%